Origin of EL3 chondrites: Evidence for variable C/O ratios during their course of formation—A state of the art scrutiny. (6th March 2017) - El Goresy, A.; Lin, Y.; Miyahara, M.; Gannoun, A.; Boyet, M.; Ohtani, E.; Gillet, P.; Trieloff, M.; Simionovici, A.; Feng, L.; Lemelle, L.
Abstract: Mineral inventories of enstatite chondrites; (EH and EL) are strictly dictated by combined parameters mainly very low dual oxygen ( f O2 ) and sulfur ( f S2 ) fugacities. They are best preserved in the Almahata Sitta MS‐17, MS‐177 fragments, and the ALHA 77295 and MAC 88136 Antarctic meteorites. These conditions induce a stark change of the geochemical behavior of nominally lithophile elements to chalcophile or even siderophile and changes in the elemental partitioning thus leading to formation of unusual mineral assemblages with high abundance of exotic sulfide species and enrichment in the metallic alloys, for example, silicides and phosphides. Origin and mode of formation of these exotic chondrites, and their parental source regions could be best scrutinized by multitask research experiments of the most primitive members covering mineralogical, petrological, cosmochemical, and indispensably short‐lived isotopic chronology. The magnitude of temperature and pressure prevailed during their formation in their source regions could eventually be reasonably estimated: pre‐ and postaccretionary could eventually be deduced. The dual low fugacities are regulated by the carbon to oxygen ratios estimated to be >0.83 and <1.03. These parameters not only induce unusual geochemical behavior of the elements inverting many nominally lithophile elements to chalcophile or even siderophile or anthracophile. Structure and mineral inventories in EL3 and EH3 chondrites are fundamentally different. Yet EH3 and EL3 members store crucial information relevant to eventual source regions and importantly possible variation in C/O ratio in the course of their evolution. EL3 and EH3 chondrites contain trichotomous lithologies (1) chondrules and their fragments, (2) polygonal enstatite‐dominated objects, and (3) multiphase metal‐rich nodules. Mineralogical and cosmochemical inventories of lithologies in the same EL3 indicate not only similarities (REE inventory and anomalies in oldhamite) but also distinct differences (sinoite‐enstatite‐graphite relationship). Oldhamite in chondrules and polygonal fragments in EL3 depict negative Eu anomaly attesting a common cosmochemical source. Metal‐dominated nodules in both EL3 and EH3 are conglomerates of metal clasts and sulfide fragments in EH3 and concentrically zoned C‐bearing metal micropebbles (≥25 μm ≤50 μm) in EL3 thus manifesting a frozen in unique primordial accretionary metal texture and composition. Sinoite‐enstatite‐diopside‐graphite textures reveal a nucleation and growth strongly suggestive of fluctuating C/O ratio during their nucleation and growth in the source regions. Mineral inventories, sulfide phase relations, sinoite‐enstatite‐graphite intergrowth, carbon and nitrogen isotopic compositions of graphite, spatial nitrogen abundance in graphite in metal nodules, and last but not least 129 I/ 129 Xe and 53 Mn/ 53 Cr systematics negate any previously suggested melting episode, pre‐accretionary or dynamic, in parental asteroids.